KOMPETENSI HAKIM PADA KASUS WANPRESTASI DALAM TEORI IDEAL TYPE : STUDI KASUS AKTA PERDAMAIAN No. 911/Pdt.g/2016/PA.Btl - Maulana, Akbar; Purwati, Diana; Habibullah, Fayyad; Azzahra, Ivana Daffa; Afkarina, Izza; Sari, Linda; Hakim, Lukman; Sulastri, Sulastri (LPPM Universitas Bina Bangsa, 2025)
This research analyzes the competencies of judges in resolving disputes of wanprestasi (default) using Max Weber's ideal type theory as a framework. It posits that judges should possess the capability to impartially assess and apply the law, ensuring decisions reflect social justice while balancing the interests of both parties involved. The study highlights the significance of alternative dispute resolution methods, such as mediation and arbitration, which provide more efficient and humane solutions compared to traditional litigation. Through a case study of Mediation Agreement No. 991/Pdt.g/2016/PA.Btl, the research examines the complexities of wanprestasi disputes, emphasizing the procedural dynamics between the parties. Additionally, the study reviews existing literature to elucidate how Weber's ideal type offers a conceptual framework for understanding mediation processes. The methodology incorporates legal research with various approaches, including statutory, case, conceptual, and analytical perspectives to ensure comprehensive legal evaluation and relevance in the evolving legal landscape. The findings aim to enhance the understanding and practical implementation of mediation in wanprestasi disputes, advocating for its adoption as an effective and fair means of conflict resolution.